PROBLEMS OF SIDERITE FORMATION AND IRON ORE EPOCHS: COMMUNICATION 2. GENERAL ISSUES OF THE PRECAMBRIAN AND PHANEROZOIC ORE ACCUMULATION - Kholodov V.N.; Butuzova G.Yu. (My University, 2004)
It is shown that peat bogs, which accumulate coal- and siderite-bearing sediments, serve as a generator of ferruginous solutions with the significant part of Fe migrating from them in the form of metalloorganic compounds. The stability of organic Fe-bearing complexes provides favorable conditions for the late diagenetic–catagenetic siderite formation in adjacent sea basins. It has been established that the formation of Phanerozoic coals, oil shales, and black shales was nearly coeval with the formation of goethite–chlorite–siderite ores. The paper discusses the influence of volcanic activity on the formation of Precambrian–Phanerozoic iron ore deposits and emphasizes the significance of siderite formation in the general evolution of the sedimentary iron ore formation.
Keywords: Precambrian; Precambrian; Докембрий